Management of Productive Waqf in Supporting the Sustainability Development Goals (SDGs) in Indonesia: A Case Study of Dompet Dhuafa - Aufaa Anjani Rasyiedah; Hartutik Hartutik (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to explore Dompet Dhuafa's productive waqf management strategy and its contribution to the achievement of the Sustainable Development Goals (SDGs), particularly goal 1 (no poverty) and goal 10 (reduced inequality). This research uses a descriptive qualitative approach with an interpretive paradigm. Data collection techniques were conducted through semi-structured interviews with Dompet Dhuafa waqf managers and beneficiaries of one of the programs in the Madina Zone, namely Teras Madina, field observations, and documentation studies. The results show that Dompet Dhuafa manages productive waqf through structured stages, including feasibility study, business plan, sharia supervision by DPS, to business implementation and profit sharing from waqf surplus. The funds used in the economic program, Teras Madina, are sourced from productive waqf and managed through a sustainable business unit. This program has a real impact on the beneficiaries, such as small traders who previously did not have a fixed business place or a stable income. After joining, they are able to increase their income to meet household needs, and with the training from the program, they can improve their entrepreneurial skills. Dompet Dhuafa also applies a collaborative approach by creating waqf forums, partnering across sectors, and encouraging quick-win innovations and long-term business plans. Transparency is maintained through regular reports and direct involvement of the wakif in monitoring activities. With this approach, productive waqf shows real potential as an instrument of economic empowerment that supports sustainable development.